Isolation, characterization and virulence assessment of Type 1d CP bovine viral diarrhea virus originating from Inner Mongolia, China - Hao, Luyao; Zhao, Fengmiao; Guo, Ting; Gao, Yuan; Hao, Yongqing (Frontiers in Veterinary Science, 2025)
In recent years, bovine viral diarrhea virus (BVDV) has been associated with increased respiratory and gastrointestinal diseases in cattle. Comprehensive monitoring and investigations into the virus's pathological features are crucial for developing effective prevention strategies. This study investigated BVDV prevalence and pathogenicity in farms undergoing elimination protocols, with a focus on characterizing a novel Cytopathic Bovine Viral Diarrhea Virus (CP-type BVDV) strain (HH839) isolated from a symptomatic calf in Hohhot, Inner Mongolia. During 2021 and 2022, 103 bovine samples were screened for BVDV via nucleic acid detection. Positive cases underwent viral isolation using MDBK cells. The HH839 strain was analyzed for cytopathic effects, ultrastructure (electron microscopy), antigenicity (serum neutralization), and genetic lineage (whole genome sequencing). Pathogenicity of Cytopathic Bovine Viral Diarrhea Virus (CP-type BVDV) infected group, Noncytopathic Bovine Viral Diarrhea Virus (NCP-type BVDV) infected group, and the mixed-infection group of CP-type and NCP-type BVDV was evaluated in New Zealand White rabbits, with viral distribution and histopathological damage assessed in multiple organs. We identified 33 positive BVDV nucleic acid cases, resulting in a positivity rate of 32.04%. Five strains of NCP-type BVDV were isolated, yielding a 15.15% separation rate, alongside one strain of CP-type BVDV with a separation rate of 3.03%. The CP strain HH839 was isolated from a severely symptomatic calf in Hohhot, Inner Mongolia. The HH839 strain demonstrated significant cytopathic effects in MDBK cells, including cellular crumpling and syncytia formation, with a concentration of 5.23 log10TCID50/0.1 mL. Electron microscopy revealed a spherical morphology with a diameter of 40–60 nm. Genetic analysis indicated a close relationship with the BVDV FBS-D8 strain from the BVDV-1d subtype. Pathogenicity trials showed slight fever and minor body weight loss in infected subjects, with BVDV detected in the trachea, lungs, spleen, and small intestines, predominantly in the spleen. The isolation of HH839, a pathogenic CP-type BVDV-1d strain, underscores the coexistence of multiple BVDV biotypes in regional cattle populations. Enhanced pathogenicity observed in mixed infections highlights complex viral interactions. These findings emphasize the necessity for sustained surveillance and biotype-specific control strategies to mitigate BVDV-associated economic losses in livestock industries.